Numerical modeling and simulation of material removal in laser drilling of thin metal sheets using meshfree collocation methods / Diaa Abdelmonem Mahmoud Abidou - Diaa Abdelmonem , Mahmoud Abidou (2017)
A simplified lightweight numerical model is proposed for predicting the hole geometry in laser drilling of thin metal sheets. A 2D axisymmetric model for transient metal laser drilling is adopted, and three different meshfree collocation methods are employed and compared with each other in terms of computational efficiency and results accuracy. Collocation discretization (i.e. strong-form) of meshless local Petrov-Galerkin (MLPG), symmetric smoothed particle hydrodynamics (SSPH) and radial point interpolation method (RPIM) is used to harness its advantages of significant reduction in computational time and constructing global matrices in a straightforward manner over their weak-form. The 2D domain is discretized into a finite number of particels, then shape functions of the neighbors are obtained. Laser beam is assumed to be continuous wave with Gaussian distribution, while particles are assumed to be removed upon reaching the melting temperature under the effect of a highly pressurized assist gas. MATLAB code is constructed for numerical simulation, and results are compared with previously published relevant work. A good agreement is shown for each method with little deviation of hole geometry prediction from each other. SSPH is chosen as the best method for the proposed work since it is significantly superior to MLPG and RPIM in terms of CPU time. Despite considering a fixed value for laser absorptivity, the proposed numerical model is shown to be computationally efficient and accurate standalone platform for predicting the penetration depth of laser drilling of thin metal sheets. The computational efficiency of meshfree collocation methods is exploited to build a lightweight standalone application with graphical user interface (GUI). This application has the potential of integrating the present model into the front panel of typical laser processing machines in order to provide an estimation of the keyhole geometry for arbitrarily given process parameters and target metals, which saves unnecessarily time-consuming and costly experimentation.